Early visual language skills affect the trajectory of literacy gains o ver a three-year period of time for preschool aged Deaf children who e xperience signing in the home - Allen, Thomas E.; Morere, Donna A. (PloS One, 2020)
Previous research has established a correlation between literacy skill s and sign language skills among deaf children raised in signing famil ies, but little research has examined the impact of early signing skil ls on the rate of growth of emergent literacy in early childhood. A su bset of data was extracted from a larger dataset containing national l ongitudinal data from a three-year investigation of early literacy dev elopment of deaf children who were between the ages of three and six a t the outset of the study. Selection criteria for inclusion in this li mited sample included: 1) being rated as having little or no access to spoken language and 2) being raised in homes in which signs were regu larly used as a means of communication (N = 56). Our purpose was twofo ld: 1) to examine and describe the trajectories of growth in letter an d word identification skill for this sample in relation to the partici pants' initial ages; and 2) to assess the degree to which the presence or deaf parents in the home (DoD) and the receptive American Sign Lan guage (ASL) skills of the participants impacted both the level of emer ging print literacy and its rate of growth over the three year period. We hypothesized that both the presence of a deaf parent in the home a nd the acquisition of ASL skills, a strong native language, would cont ribute to both the overall letter and word identification skills and t o the rates of growth of this skill over time. Results indicated that having a deaf parent did, indeed, impact emergent literacy attainment, but its effect was rendered nonsignificant when ASL skill was taken i nto consideration. Possession of stronger ASL skills, whether or not t he children had deaf parents, contributed significantly to both the le vels and rate of growth. The findings contribute to the body of work t hat emphasizes the importance early language skills (spoken or signed) to later academic success and dispels the myth that deaf children wit h deaf parents have exclusive access to the acquisition of these skill s.
Keywords: Child; Child Language; Child; Preschool; Deafness; Female; Humans; Language Development; Literacy; Longitudinal Studies; Male; Parents; Reading; Sign Language